School Students’ Motivation for Learning Sciences: How is it Influenced by Self-confidence in Science and Inquiry-based Teaching Approach? - Pečiuliauskienė, Palmira; Belakoz, Alena (Pedagogika, 2019)
The article deals with the Lithuanian school students’ motivation for learning science on the basis of TIMSS 2015 data. This article analyses the influence of two factors on motivation for learning science: the self-confidence in science of school students’ and teaching science using inquiry-based approach. The purpose of the research is to analyze the influence of self-confidence in science and the influence of teaching science by inquiry approach on students’ motivation for learning science.